2020
DOI: 10.1242/jeb.237727
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Free from Thermodynamic Constraints: Thermal Acclimation and Metabolic Compensation in a freshwater zooplankton species

Abstract: Ectothermic organisms’ respiration rates are affected by environmental temperatures, and sustainable metabolism at high temperatures sometimes limits heat tolerance. Organisms are hypothesized to exhibit acclimatory metabolic compensation effects, decelerating their metabolic processes below Arrhenius expectations based on temperature alone. We tested the hypothesis that either heritable or plastic heat tolerance differences can be explained by metabolic compensation in the eurythermal freshwater zooplankton c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…Analogous to the prediction of ‘thermal compensation’, the individual from warm environments would depress the metabolic rate relative to siblings from cold environment by plasticity (e.g. Caldwell, 1969; Coggins et al., 2020; Scheffler et al., 2019), the resting metabolic rates of the hatchlings in this study were downregulated by warming incubation conditions and further depressed by warming husbandry conditions, especially at higher body temperatures (Figure 4). The ‘live (grow) fast, die young’ scenario claims that faster life‐history rates, normally indicated by higher metabolic rates, will induce shorter longevity or survival rates (Bestion et al., 2015; Speakman, 2005; Speakman & Garratt, 2014).…”
Section: Discussionsupporting
confidence: 71%
“…Analogous to the prediction of ‘thermal compensation’, the individual from warm environments would depress the metabolic rate relative to siblings from cold environment by plasticity (e.g. Caldwell, 1969; Coggins et al., 2020; Scheffler et al., 2019), the resting metabolic rates of the hatchlings in this study were downregulated by warming incubation conditions and further depressed by warming husbandry conditions, especially at higher body temperatures (Figure 4). The ‘live (grow) fast, die young’ scenario claims that faster life‐history rates, normally indicated by higher metabolic rates, will induce shorter longevity or survival rates (Bestion et al., 2015; Speakman, 2005; Speakman & Garratt, 2014).…”
Section: Discussionsupporting
confidence: 71%
“…Our finding also underlines that larger individuals inhabiting the lower latitudinal boundary of their distributional range were subject to metabolic homeostasis ( sensu Precht et al, 1973 ), in which their metabolic rates were independent of temperature beyond the current local maxima. Several studies have shown that when facing changes in temperature, often beyond that of their usual environment ( Coggins et al, 2021 ), metabolic homeostasis might occur in aquatic ectotherms ( Bullock, 1955 ; Fangue et al, 2009 ; Precht et al, 1973 ; Seibel et al, 2007 ; Young, 1979 ). This results in a degree of homeostasis at the cellular level, enabling organisms to maintain their functions in spite of temperature change ( Precht et al, 1973 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial potential was measured by means of rhodamine-123 staining in neonates born to either young or old mothers treated as described above. Newborns <12 h old were placed in groups of 5 into 1.5 mL tubes containing 0 -10 uM rhodamine-123 in COMBO water for 24 hours (Emaus et al 1986;Coggins et al 2021a). The fluorescence was measured with Leica DM3000 microscope with a 10x objective (0.22 aperture) equipped with Leica DFc450C camera using the 488 nm excitation / broadband (>515 nm) emission filter.…”
Section: Mitochondrial Potential Measurementsmentioning
confidence: 99%